Analisis Kelayakan Bisnis Pada UMKM Mie Ngonah - Agus Sutardi; Ajeng Reni Razmayanti; Meira Purnama Rizki; Rizky Syaifullah; Shapdani Anggara Priyadi; Yumita Sari Dianti (Jurnal Manajemen Riset Inovasi, 2024)
This article or writing aims to find out "business feasibility analysis for Ngonah Noodle". The problem focuses on various aspects in measuring how feasible this ngonah noodle business is to be implemented. As is known, the city of Bandung is a city that has the nickname "culinary paradise". This is what underlies the habits of its people who really like culinary delights. The large number of MSMEs in the city of Bandung, especially in the food sector, makes the city of Bandung a destination for people outside the city for culinary delights. One of the culinary delights that is currently popular and sought after by many people is spicy noodles. Ngonah Mie UMK is an UMK that makes and innovates products from spicy noodles. This MSME not only produces processed spicy noodles but also various other types of food or snacks such as aci meatballs and dumplings. Ngonah Noodles UMKM has a good structure and system in all aspects that support its business. Even though it was founded not long ago, this ngonah noodle business is actually able to compete with competitors who sell similar products.